Re‐evaluation of stannous chloride (E 512) as food additive. (25th June 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; et al.
Abstract: The Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of stannous chloride and stannous chloride dihydrate (E 512) as food additives. The Panel considered that adequate exposure and toxicity data were available. Stannous chloride is only permitted as food additives in one food category and no reply on the actual use level of stannous chloride (E 512) as a food additive and on its concentration in food was provided by any interested party. According to the Mintel's Global New Products Database (GNPD), stannous chloride was not labelled on any products in the EU nor in Norway. The regulatory maximum level exposure assessment scenario is based on the maximum permitted levels (MPLs) for stannous chloride (E 512), which is 25 mg Sn/kg. The mean exposure to stannous chloride (E 512) from its use as a food additive was below 1.3 μg Sn/kg body weight (bw) per day for all age groups. The 95th percentile of exposure to stannous chloride (E 512) ranged from 0.0 μg Sn/kg bw per day in all groups to 11.2 μg Sn/kg bw per day in adults. Absorption of stannous chloride from the gastrointestinal tract is low there is no concern with respect to carcinogenicity and genotoxicity. Gastrointestinal irritation was reported in humans after ingestion of a bolus dose of 40 mg Sn. The Panel concluded that stannous chloride (E 512) is of no safety concern in this current authorised use and use levels.